Frequency Scanning Conformal Sensor Based on SIW Metamaterial Antenna - Celenk, Esra; Tokan, Nurhan Turken (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
A conformal transverse slotted substrate integrated waveguide (SIW) metamaterial leaky-wave antenna sensor with uniform slots is investigated and analyzed for mmWave sensing applications. Firstly, its planar version is introduced. Then, its performance is compared with the curved SIW antenna. The metamaterial characteristics of the antennas are investigated. The transverse slots on the array forms a composite right/left-handed (CRLH) metamaterial structure that controls the radiation direction as the function of frequency. It behaves like a left handed metamaterial and radiates backward in the lower frequencies of the band (28-45GHz), whereas it behaves like a right handed metamaterial that scans forward direction at the higher frequencies (45-62GHz). Approximately 80 degrees beam scanning is obtained in curved version with acceptable side lobe levels, whereas 110 degrees beam steering is achieved with the planar version. Theoretical analysis and the simulation results are confirmed successfully by the experimental results in the 28-40 GHz band. Besides, a practical example of conformal SIW metamaterial antenna on military helmet made of a ballistic material is illustrated. The calculated spatial peak power density values of the proposed curved SIW metamaterial antenna on the outer surface of a head phantom are demonstrated.
Keywords: Curved SIW; leaky wave radiation; leaky antenna; metamaterial antenna sensor; substrate integrated waveguide; SIW antenna; SIW sensor; INTEGRATED WAVE-GUIDE; COMPOSITE PAPER; ARRAY; LOSSES; Engineering; Instruments & Instrumentation; Physics